Minimally Invasive Direct Lateral Approach to the Thoracolumbar Junction: Cadaveric Analysis and Case Illustrations - Straus, David; Takagi, Ippei; O'Toole, John (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background Multiple surgical exposures to the thoracolumbar junction have been described. The minimally invasive direct lateral approach to the lumbar spine captures the advantages of anterolateral approaches while minimizing soft tissue destruction and perioperative morbidity. Utilizing this approach at the thoracolumbar junction presents unique anatomical challenges posed by the ribs, diaphragm, pleura, and lung.Methods We examine the use of a minimally invasive direct lateral approach to the thoracolumbar junction (T10–L2) through six cadaveric approaches and provide case examples of three patients.Results In six approaches with normal spinal alignment we were able to access all disc spaces in the thoracolumbar region. The L2–L3 disc was accessed below the 12th rib in 100% of spines; L1–L2 accessed through the T11–T12 intercostal space in 83% of spines; T12–L1 was accessed through the T11–T12 intercostal space in 67% of spines and through the T10–T11 intercostal space in 33% of spines; T11–T12 was accessed through the T10–T11 intercostal space in 83% of spines; finally, T10–T11 was accessed through the T10–T11 intercostal space in 67% of spines and through the T9–T10 intercostal space in 33% of spines.Discussion The minimally invasive direct lateral approach offers access to ventral pathology at the thoracolumbar junction. Familiarity with common anatomical structures encountered during this approach in the thoracolumbar junction enhances surgical planning and facilitates surgical exposure.
Keywords: direct lateral interbody fusion; thoracolumbar junction; minimally invasive spine surgery; XLIF; DLIF